Nationhood and the (De)Construction of Mythical England in Ben Wheatley’s Kill List - Diana Ortega Martin (Amaltea: Revista de Mitocrítica, 2023)
Arthurian mythology has often been employed to articulate notions of nationhood, identity, and nationalism. In the recent wave of nationalist nostalgia, myths, such as Arthur’s, have been put forth as core narratives to return to, articulating the longing for a primitivist, pastoral, pre-modern England. The post-Brexit landscape has seen a rise of neo-imperialism, more obvious in so-called ‘global Britain’ / ‘Renaissance England’, overlooking how Britain and its polarisation seem to be closer in spirit now to the Civil War than to the times of hegemonic splendour. This article analyses how Wheatley’s 2011 Kill List reappropriates Arthurian mythology by subverting its usual purpose of reaffirming a hegemonic sense of nationhood. The analysis uses three main methods: defining myth in contemporary England and its cultural products, establishing a correlation between Folk Horror and the Arthurian legend, and studying Arthurian myths and motifs present in the film and their significance. It ultimately concludes that the Arthurian myth is used to question the blinding embrace of national mythology and the darker face of England’s nationhood.